2012
DOI: 10.1021/ic300036y
|View full text |Cite
|
Sign up to set email alerts
|

Triclinic–Cubic Phase Transition and Negative Expansion in the Actinide IV (Th, U, Np, Pu) Diphosphates

Abstract: The AnP(2)O(7) diphosphates (An = Th, U, Np, Pu) have been synthesized by various routes depending on the stability of the An(IV) cation and its suitability for the unusual octahedral environment. Synchrotron and X-ray diffraction, thermal analysis, Raman spectroscopy, and (31)P nuclear magnetic resonance reveal them as a new family of diphosphates which probably includes the recently studied CeP(2)O(7). Although they adopt at high temperature the same cubic archetypal cell as the other known MP(2)O(7) diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The XRD patterns (Figure 1) first confirmed that rhabdophane precursors crystallize in the monoclinic C2 structure as reported in our previous study [30]. Moreover, the pellets obtained after sintering were systematically found to be single-phase monazite-cheralite solid solutions (Monoclinic P2 1 /n) [31], as no secondary phase, such as -ThP 2 O 7 [32], -Th 2 (PO 4 )(P 3 O 1O ) [33], -Th 4 (PO 4 ) 4 (P 2 O 7 ) [34] or Nd(PO 3 ) 3 [35] was detected. As the conditions chosen constitute the most extreme used in this work in terms of temperature and heat duration, this result then ensures that single-phase samples will be obtained whatever the operating conditions.…”
Section: Characterization Of Powders and Pellet Samplessupporting
confidence: 83%
“…The XRD patterns (Figure 1) first confirmed that rhabdophane precursors crystallize in the monoclinic C2 structure as reported in our previous study [30]. Moreover, the pellets obtained after sintering were systematically found to be single-phase monazite-cheralite solid solutions (Monoclinic P2 1 /n) [31], as no secondary phase, such as -ThP 2 O 7 [32], -Th 2 (PO 4 )(P 3 O 1O ) [33], -Th 4 (PO 4 ) 4 (P 2 O 7 ) [34] or Nd(PO 3 ) 3 [35] was detected. As the conditions chosen constitute the most extreme used in this work in terms of temperature and heat duration, this result then ensures that single-phase samples will be obtained whatever the operating conditions.…”
Section: Characterization Of Powders and Pellet Samplessupporting
confidence: 83%
“…While SiP 2 O 7 , TiP 2 O 7 , and HfV 2 O 7 indeed adopt a cubic 3 × 3 × 3 superstructure, NMR and high resolution synchrotron studies have shown that the symmetry is lower for many materials. For example, SnP 2 O 7 and GeP 2 O 7 were found to be monoclinic [100,101,102], CeP 2 O 7 and AnP 2 O 7 (An = U, Th, Pu, Np) were reported as triclinic [103,104], and ZrP 2 O 7 and HfP 2 O 7 exhibit an orthorhombic distortion [105,106]. The structure of the latter compounds was solved independently from synchrotron single crystal and powder diffraction data by the Birkedal and Evans groups, and consists of a 136 atom unit cell in space group Pbca.…”
Section: Negative Thermal Expansion Due To Transverse Vibrationsmentioning
confidence: 99%
“…All P-O-P bond angles are significantly smaller than 180°, eliminating the possibility of transverse oxygen vibrations that could lead to a unit cell contraction [105,106]. However, high resolution studies of AnP 2 O 7 have shown that NTE can be observed at high temperature in materials with bent P-O-P units [104]. Interestingly, SnP 2 O 7 does not adopt the ideal ZrV 2 O 7 structure at all, but undergoes a series of different distortions up to its decomposition temperature.…”
Section: Negative Thermal Expansion Due To Transverse Vibrationsmentioning
confidence: 99%
“…2 Negative thermal expansion is also observed in the high-temperature cubic phase of various actinide phosphates, like AP 2 O 7 (A = Th, U, Np, Pu). 46 The ambient-temperature triclinic phase of such actinide diphosphate transforms to the cubic phase with a large expansion of the unit cell volume. The abrupt increase in unit cell volume at the transition leads to a relatively open structure having a lower packing density which allows lower or negative expansion in the lattice.…”
Section: Theoretical Calculationsmentioning
confidence: 99%